2006
DOI: 10.1126/science.1133781
|View full text |Cite
|
Sign up to set email alerts
|

Selective Etching of Metallic Carbon Nanotubes by Gas-Phase Reaction

Abstract: Metallic and semiconducting carbon nanotubes generally coexist in as-grown materials. We present a gas-phase plasma hydrocarbonation reaction to selectively etch and gasify metallic nanotubes, retaining the semiconducting nanotubes in near-pristine form. With this process, 100% of purely semiconducting nanotubes were obtained and connected in parallel for high-current transistors. The diameter- and metallicity-dependent "dry" chemical etching approach is scalable and compatible with existing semiconductor proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
425
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(441 citation statements)
references
References 22 publications
14
425
1
1
Order By: Relevance
“…Advances in the SWNTs growth, [54,55] etching [147] and separation [64][65][66][67][68][69][70] processes could further improve nanotube-uniformity in terms of removing metallic SWNTs. Sem-enriched SWNTs with defined (n, m) chirality can be engineered to have their E ii transitions lined up appropriately with either the thin metal-plasmon resonance or the redox levels of analyte under investigation to further enhance sensitivity.…”
Section: Future Outlook and Concluding Remarksmentioning
confidence: 99%
“…Advances in the SWNTs growth, [54,55] etching [147] and separation [64][65][66][67][68][69][70] processes could further improve nanotube-uniformity in terms of removing metallic SWNTs. Sem-enriched SWNTs with defined (n, m) chirality can be engineered to have their E ii transitions lined up appropriately with either the thin metal-plasmon resonance or the redox levels of analyte under investigation to further enhance sensitivity.…”
Section: Future Outlook and Concluding Remarksmentioning
confidence: 99%
“…Integration of nanotube devices into circuits may become a reality in the near future, if we are able to produce carbon nanotubes with desired dimensions and properties [54,55]. In this context, DWCNTs could be ideal candidates for nanowires if they have a semiconductor-metallic configuration for the outer and inner constituent layers.…”
Section: Field-effect Transistorsmentioning
confidence: 99%
“…86 Independent density functional theory calculations have shown that semiconducting singlewalled nanotubes have a lower heat of formation, 53 while unique impurity states near the Fermi level of m-CNTs act as a strong scattering center, 87 both of which result in m-CNTs being more reactive than s-CNTs. 37 Additionally, it is known that the atmospheric oxygen and water can cause charge transfer and trapping, which can affect the behavior of s-CNT and m-CNT devices differently. 75 It is important to note that our samples have cobalt catalyst present.…”
Section: Articlementioning
confidence: 99%
“…One factor is the lower enthalpy of formation of semiconductors, 37,53 while another factor may be the presence of delocalized electronic states and separately the smaller ionization potential. 22,26,37,38 The presence of electronic states near the Fermi level for metals and the differences in work function 54,55 between semiconductors and metals are very important for the selectivity of chemical reactions. 26,55À57 In other studies the opposite trend, with semiconductors being preferentially etched, has been observed, including those involving H 2 O 2 as an oxidant.…”
mentioning
confidence: 99%